Hybrid repair of aortic aneurysm in a patient with a congenital pelvic kidney - Halli Krzyzaniak, MD, BSc; Naomi Wedel, MD, BSc; Ali Fatehi Hassanabad, MD, PhD; Richard Cormack, MD, FRCPC; Kenton Rommens, MD, FRCSC (Journal of Vascular Surgery Cases and Innovative Techniques)
We describe a patient with an asymptomatic infrarenal abdominal aortic aneurysm. Treatment decisions were complicated by the presence of a left congenital pelvic kidney supplied by two renal arteries originating from the proximal common iliac arteries bilaterally and respiratory status that was prohibitive to open repair. A hybrid surgical repair was performed with a bifurcated aortic endograft and parallel grafting to revascularize the pelvic renal arteries. This procedure was combined with a right common iliac endovascular occlusion and femoral-femoral bypass. This case adds to the limited reports of endovascular management of patients with concomitant aneurysmal disease and ectopic kidneys.